THE EFFECT OF SILICON ON MORPHOLOGICAL TRAITS AND MECHANICAL PROPERTIES OF POLYGONATUM MULTIFLORUM (L.) ALL. ‘VARIEGATUM’ CUT SHOOTS - Elżbieta Pogroszewska; Paweł Szot; Katarzyna Rubinowska; Aleksandra Konopińska-Mamej; Alicja Świstowska; Adam Zdybel; Marzena Parzymies; Wojciech Durlak (Acta Scientiarum Polonorum: Hortorum Cultus, 2019)
Garden perennials are a source of floristry material produced in field or under covers. A perennial producing long, leafy shoots, which in flower arrangements might successfully substitute fern or palm leaves, is Polygonatum multiflorum. The variety characterizing with decorative white margined leaves is ‘Variegatum’. To improve their quality, the growth stimulator Actisil Hydro Plus, which contains 0.6% of active silicon in a form of orthosilicic acid was applied. The aim of the conducted experiment was to estimate the influence of silicon and a place of cultivation (tunnel and open field) on post-harvest quality determined with morphological features, vase life longevity and mechanical properties of Polygonatum multiflorum (L.) All. ‘Variegatum’ stems. The plants were sprayed with water solutions of Actisil in concentrations: 0.2%, 0.3%, and 0.4%, six times during the growing season in weekly intervals, starting from the first decade of May, always in the morning. It was stated that cultivation of Polygonatum in the unheated foil tunnel increases quality of shoots for cut greenery, determined with morphological features and post-harvest longevity. Cultivation of Polygonatum in a foil tunnel and spraying plants with Actisil in concentrations of 0.3 or 0.4% is advantageous due to possibility to increase a number of shoots from 20% to over 31%, their length from 9% to 11% and fresh weight from 52% to 71%, in comparison to control plants. It is advised to treat plants cultivated in a tunnel, with Actisil in concentration of 0.4% as it improved shoots quality evaluated with their diameter and lower leaves blade area. Spraying plants with Actisil in concentrations of 0.2–0.4% in the tunnel and 0.2% in field prolongs post-harvest shoots longevity by 3–4 days. Plants cultivated in the tunnel characterize with higher strength of shoots determined with higher maximum force causing permanent damage and lower stem deflection than plants cultivated in field. Plants grown in a tunnel and sprayed with Actisil in concentrations of 0.4% characterized with the strongest shoots after 14 days of storage, however a similar effect was observed with the concentration of 0.3% and in case of plants cultivated in field and sprayed with 0.4% of Actisil.